THE CORRELATION BETWEEN TEACHERS’ TEACHING STYLE AND STUDENTS’ LEARNING MOTIVATION - Sindirella, Putri; Samtidar, Samtidar; Sakkir, Geminastiti (JTechLP: Journal of Technology in Language Pedagogy, 2025)
This study aims to determine whether there is a significant correlation between teachers' teaching style and students' learning motivation in learning English at SMPN 27 Makassar. The variables in this study consisted of teachers' teaching style as the independent variable (X) and students' learning motivation as the dependent variable (Y). The population of the study was all VIII-grade students of SMPN 27 Makassar, totaling 313 students, with a research sample of 35 students from class VIII.8 selected using the purposive sampling technique. The instrument used was a Likert scale-based closed questionnaire, each consisting of 15 items for teacher teaching style and 16 items for student learning motivation. The data were analyzed using the Pearson product-moment correlation statistical technique to determine the closeness of the correlation between variables. The results of the analysis show that the calculated r count is 0.587, while the r table at the 5% significance level with N = 35 is 0.344. Because r count (0.587) > r table (0.344), it can be concluded that there is a significant correlation between teacher teaching style and student learning motivation. This study concludes that teachers' teaching style has an important role in increasing students' learning motivation.